Defining the Exposome Using Popular Education and Concept Mapping With Communities in Atlanta, Georgia - Lebow-Skelley, Erin; Young, Lynne; Noibi, Yomi; Blaginin, Karla; Hooker, Margaret; Williamson, Dana; Tomlinson, Martha Scott; Kegler, Michelle C.; Pearson, Melanie A. (Frontiers in Public Health, 2022)
Introduction The exposome concept provides a framework to better incorporate the environment into the study of health and disease and has been defined by academics to encompass all lifetime exposures including toxicants, diet, and lifestyle choices. However, initial applications of the exposome concept have been less apt at measuring social determinants of health, focusing primarily on conventional environmental exposures and lifestyle choices that do not reflect the complex lived experience of many communities. To bring community voice into the exposome concept, the HERCULES Exposome Research Center and its Stakeholder Advisory Board co-developed the Exposome Roadshow. We present and discuss the resulting community-exposome definition to inform and improve exposome research. Materials and Methods Four communities from distinct areas across metro-Atlanta participated in separate two-day Exposome Roadshow workshops with concept mapping. Aligned with a popular education approach in which community knowledge is used to work collectively for change, concept mapping provided a systematic method to collect and visualize community members’ knowledge and create a shared understanding to take action. Community members brainstormed, sorted, and rated their responses to the prompt: “What in your environment is affecting your and your community’s health?” Responses were analyzed and visually depicted by concept maps consisting of separate but interrelated clusters of ideas. Community members discussed and validated the maps, selecting a final map illustrating their community’s exposome. Results A total of 118 community members completed concept mapping. On average communities identified 7 clusters to define their exposome. The resulting concept maps offer a community definition of the exposome. Five major themes arose across all four communities: conventional environmental concerns, built environment, social relationships, crime and safety, and individual health and behaviors. Discussion The resulting community-exposome definition demonstrates the importance of expanding the scope of exposures beyond traditional environmental influences to include the lived experience of individuals and communities. While newer exposome definitions align more closely with this community definition, traditional exposome methods do not routinely include these factors. To truly capture the totality of lifetime exposures and improve human health, researchers should incorporate community perspectives into exposome research.